2014
DOI: 10.1039/c4ra07031c
|View full text |Cite
|
Sign up to set email alerts
|

Selenium substitution endows cystine with radiosensitization activity against cervical cancer cells

Abstract: Selenium substitution could endow cystine the radiosensitization activity against cervical cancer HeLa cells through overproduction of ROS and activation of downstream signaling, which suggests this could be a novel strategy for design of cancer radiosensitizers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…A previous study demonstrated that the anticancer activity of selenium compounds occurred via oxidation of reduced glutathione and other thiols, which also revealed apoptogenic effects and alterations in cell cycle progression mediated by ROS [ 53 ]. Furthermore, Xie and collaborators [ 54 ] showed that a selenium compound could be a strategy for design and further development into effective and low toxicity cancer radiosensitizers, as selenium substitution significantly enhanced X-ray-induced ROS overproduction in cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study demonstrated that the anticancer activity of selenium compounds occurred via oxidation of reduced glutathione and other thiols, which also revealed apoptogenic effects and alterations in cell cycle progression mediated by ROS [ 53 ]. Furthermore, Xie and collaborators [ 54 ] showed that a selenium compound could be a strategy for design and further development into effective and low toxicity cancer radiosensitizers, as selenium substitution significantly enhanced X-ray-induced ROS overproduction in cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…In the past decades, a great number of studies demonstrated that Se species are promising agents for cancer therapeutics, due to their capability of generating reactive oxygen species (ROS), which can induce apoptosis in tumor cells . Interestingly, Se‐containing compounds combined with radiotherapy appeared to specifically enhance the radiosensitivity of cancer cells resulting in a wave of selenium related publications . It needs to be mentioned that the mechanism of action of selenium is still not well‐understood.…”
Section: Enhancing the Effect Of Ionizing Radiationmentioning
confidence: 99%
“…[88,89] Interestingly, Secontaining compounds combined with radiotherapy appeared to specifically enhance the radiosensitivity of cancer cells resulting in a wave of selenium related publications. [90][91][92] It needs to be mentioned that the mechanism of action of selenium is still not well-understood. An increase in ROS levels was observed when combining Se compounds with radiotherapy, which is not necessarily only related to the production of secondary electrons, but may have a different origin.…”
Section: Selenium Nanocarriersmentioning
confidence: 99%
“…(Tiekink, 2012). Selenium can act as an effective radiosensitizer to enhance the anticancer efficacy through induction of cancer cell apoptosis (Xie, He, Lai, Zheng, & Chen, 2014). Motivated by the potential utility of selenium and tellurium against a number of diseases and pathological conditions, we have undertaken this study in order to fill the gap in structural characteristics of the two substituted tri-peptides.…”
Section: Figure 1 Schematic Representation Of Gshmentioning
confidence: 99%